Implementation of Application for Recognition of Illegitimate Children Based on Judge's Determination (Religious Court Determination Study Number 161/PDT.P/2023/PA.TNK) - Bachri, Erlina; Utami, Adelya Putri (CV. Rayyan Dwi Bharata, 2024)
Marriage as an action that drives the development of life does not only apply to humans, but also plants and animals. Marriage defines marriage as a physical and spiritual bond between a man and a woman to form a happy and eternal family, based on belief in the Almighty God. The purpose of marriage, among other things, is to produce offspring. Children are considered a gift and responsibility that must be supervised because they have value, position and rights as human beings. Children's rights are recognized in the 1945 Constitution and the Child Protection Law, but children born out of wedlock face legal challenges regarding their status and rights. This article highlights the legal problems of children outside of marriage. Children born out of wedlock have a complex legal status and are often not recognized in aspects of care, inheritance rights and the validity of the birth certificate. This has a major impact on the child's welfare and is a burden for the mother and her family. The application process for determining the origin of children outside of marriage in Indonesia is regulated in the Marriage Law. This research focuses on the implementation of requests for recognition of illegitimate children through a case study of Religious Court Determination Number 161/PDT.P/2023/PA.TNK. It is hoped that the research results will provide a deeper understanding of the legal process for recognizing children outside of marriage and its impact on children's rights. In addition, this research will evaluate the extent to which the legal system is able to protect the rights of children born out of wedlock and provide recommendations for further improvements in order to increase justice and legal protection for children born out of wedlock.